Seismic Monitoring of Baseflow and Groundwater Changes in the Yellowstone National Park - Bingxu Luo; Hejun Zhu; David Lumley (Geophysical Research Letters)
Abstract Relative seismic velocity changes (dv/v) are being increasingly used to monitor changes in groundwater. However, it remains challenging to verify its implementation in watersheds without direct groundwater well measurements. In this study, we conduct a 12‐year dv/v observation in a watershed of the Yellowstone National Park (YNP). We find that the seasonal fluctuations and long‐term trend of the measured dv/v are highly correlated with the estimated baseflow, which serves as a constraint for groundwater changes. We integrate the estimated baseflow into a poroelastic mechanism and conduct two dv/v simulations based on pressure diffusion. These simulations closely match with our observed dv/v variations. In addition, our analysis suggest that the measured dv/v is primarily influenced by hydrologic pressure diffusion rather than surface air temperature. We conclude that the baseflow analysis can further enhance the seismic monitoring of groundwater changes.